2017
DOI: 10.21149/7994
|View full text |Cite
|
Sign up to set email alerts
|

Cambios en los precios de bebidas y alimentos con impuesto en áreas rurales y semirrurales de México

Abstract: Objetivo. Analizar cambios en precios asociados con la implementación de los impuestos a bebidas azucaradas y alimentos no básicos con alta densidad energética imple­mentados en 2014. Material y métodos. Se recolectaron precios en áreas rurales y semiurbanas en diciembre de 2013, y abril y diciembre de 2014. Se analizaron cambios en precios por tipo de bebidas y alimento con impuesto usando modelos de efectos fijos y estratificando por región, tipo de establecimiento y tamaño de presentación. Resultados. El im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 17 publications
1
33
0
4
Order By: Relevance
“…Previous analyses have found that in urban areas the increase in price after the tax was close to 8% (Colchero et al, 2017, unpublished), but in rural areas this was 2–4% only (Colchero et al, 2017b). This suggests that there is variability in the pass-through of the tax to consumers, and it is possible that our household’s groups were exposed to different prices.…”
Section: Discussionmentioning
confidence: 93%
“…Previous analyses have found that in urban areas the increase in price after the tax was close to 8% (Colchero et al, 2017, unpublished), but in rural areas this was 2–4% only (Colchero et al, 2017b). This suggests that there is variability in the pass-through of the tax to consumers, and it is possible that our household’s groups were exposed to different prices.…”
Section: Discussionmentioning
confidence: 93%
“…The INSP along with other academic institutions, NGOs and the MOH are currently monitoring and evaluating the effect of the taxes on prices, consumption and the use of fiscal revenues for obesity‐related programs. An observational study conducted during the first year of the policy found a significant increase in the price of SSB in urban areas ; however, this was not the case in rural ones . Studies using data from urban households and national sales found a 6% reduction in the consumption of SSB in 2014 and a 9% reduction in 2015 ; consumption of nonessential energy‐dense foods decreased by 5% in 2014 among urban households .…”
Section: Results – Case Studiesmentioning
confidence: 99%
“…Meaning that the intake in these disadvantaged populations is also considerable, even if it is slightly lower. These results are worrisome, considering that Colchero and colleagues reported that the price of taxed beverages and foods increased less in rural areas, 20 and hence the effect of the tax on consumption in rural areas could be attenuated as has been already identified in the case of taxed beverages. 21 The limitations of this study are those related to the measurement error expected in self-reported dietary data, 22 as well as limitations in the of foods and beverages available in the food composition table that hinders exact classification of items as taxed or untaxed.…”
Section: Artículo Originalmentioning
confidence: 96%
“…Likewise, the exemption applies to all taxed beverages and foods (not only sweet bread); but it might affect particularly bakerymade sweet bread, which among all taxed beverages and foods is the main item generally producible in small-scale businesses. In sum, the taxes introduced in 2014 targeted items that account for a considerable portion of Mexicans' energy, added sugar and saturated fat intake (20,62, and 22% respectively). Therefore, these taxes have the potential to beneficially influence the quality of the Mexican population's diet.…”
Section: Artículo Originalmentioning
confidence: 99%